WEBSITE QUALITY MEASUREMENT OF DIPA MAKASSAR UNIVERSITY - Suci Ramadhani Arifin; Muhammad Rizal (ZONAsi: Jurnal Sistem Informasi, 2022)
Since the implementation of the Dipa Makassar University website, there has never been a measurement of the quality of the website so that the success of the service is not yet known. This study was conducted to measure the service quality of the Dipa Makassar University website with the aim of knowing the success rate of website services seen from the compatibility between the perceptions and expectations of students as website users. WebQual and Importance Performance Analysis (IPA) methods are used in this study. The results of the study prove that there is a gap between students' perceptions and expectations on each website quality dimension, where the perceived value is smaller than the student's expectations. The smallest gap lies in the quality of service interactions with a conformity level of 87.56% which indicates that website services are quite successful in the quality of service interactions. The biggest gap lies in the quality of information with a conformity level of 68.80% which indicates that website services have not met student expectations, especially the quality of information.